ANALYSIS INCOME OF BROILER FARMERS BY THE SYSTEM OF CLOSED HOUSE MAINTENANCE ON PARTNERSHIP MODEL (Case Study Plasma Sri Budi Ratini in Candikusuma Village, Melaya District, Jembrana Regency) - I G. I. K., Prawira; Mahardika, I G.; Sukanata, I W. (Jurnal Peternakan Tropika, 2017)
This research aims to analysis the farmer’s income of the broilers farm with the closed house system on the partnership models. Variables observe are investment cost, production cost, business revenue, operating income, R/C ratio and BEP business. This research used data for one year consisting of 7 production periods. The data were analyzed by quantitative descriptive analysis methods. The results showed that the investment cost is Rp 459.972.500 or Rp 41.816/tail, the average of production cost is Rp 322.804.204 per periods. The average revenue is Rp 353.650.992 per periods, theaverage income of broilers farmer reached out to Rp 20.391.337 each periods or Rp 1.020,74/kg body weight with the value of R/C ratio is 1,06. BEP of the production of broilers farm with closed house system on the partnership model is 6.771 kg body weight. BEP forselling price is equal toRp15.783/kg body weight. The results of this research showed that the performance of broilers production in closed house system on the partnership model is profitable and feasible.